PENGEMBANGAN E-MODUL PADA MATERI KONSEP JARINGAN KOMPUTER MATA PELAJARAN KOMPUTER DAN JARINGAN DASAR DI SMKS KETINTANG SURABAYA - Dea Alvanita Pangesti Pangesti; Mustaji Mustaji (Universitas Negeri Surabaya, 2023)
The purpose of this study is to determine the feasibility and effectiveness of e-module material on the concept of computer networks, computer subjects and basic networks. The development procedure used is the ADDIE model. The subjects in this study were class X Multimedia 2 as an experimental class and class X Multimedia 1 as an experimental class. The data collection method uses interviews, questionnaires and tests. To analyze data with the Normality Test using the F test, the Homogeneity Test uses the chi-squared formula and the T-Test uses the t-test formula. The experimental design used was the Pretest Posttest Control Group Design. Based on the results of data analysis from questionnaires and interviews, it can be concluded that the e-module material of the concept of computer networks is included in the category of feasible and good use in learning. While the results of data analysis of student learning outcomes show that e-modules are effective in improving learning outcomes. This can be proven by the results of the t test, t count obtained results greater than t table, namely 3.79 for t count and 1.66 for t table. Thus the e-module material on the concept of computer networks in Computer and Basic Networks subjects effectively improves the learning outcomes of class X Multimedia students